Enhancing Conceptual Understanding of Photosynthesis through Integrated 5E Inquiry-Based and Cooperative STAD Learning: A Case Study in Thailand - Bhanupong Phrommarat; Nattida Ratchaya; Nitima Phrommarat (Biosaintifika: Journal of Biology & Biology Education, 2026)
Photosynthesis is widely regarded as a conceptually complex topic in biology that many students find difficult to understand. Nonetheless, there has been limited research to explore how inquiry-based and cooperative learning can be systematically integrated to support students’ understanding. This study aimed to investigate the effects of an integrated 5E inquiry-based learning model and Student Teams Achievement Divisions (STAD) cooperative learning approach on students’ conceptual understanding of photosynthesis, cooperative learning behaviors, and learning satisfaction. A one-group pretest–posttest quasi-experimental design was employed with 62 Grade 11 students at a public secondary school in Thailand. The intervention was implemented over eight instructional hours. Research instruments included a Photosynthesis Conceptual Understanding Test, a cooperative learning behavior observation rubric, and a learning satisfaction questionnaire. Data were analyzed using paired-sample t-tests, effect size (Cohen’s d), normalized gain (g), and descriptive statistics. The results showed a significant improvement in conceptual understanding, with a very large effect size (d = 1.88) and a medium-to-high normalized gain (g = 0.62). Students also presented high levels of cooperative learning behaviors and very high learning satisfaction. The results indicate that embedding STAD within the 5E inquiry cycle can potentially support both cognitive and social dimensions of learning as well as provide a practical framework for teaching complex biological concepts. This research supports SDG 4 (Quality Education) and SDG 13 (Climate Action) by promoting effective, student-centered learning through inquiry and cooperation, while enhancing students’ understanding of photosynthesis and its role in climate change, and developing the skills needed to address future sustainability challenges.